Utilización de materias primas regionales en la alimentación de equinos criollos adultos en el municipio de Villavicencio (Orinoquia, 2007)
Titulo en ingles: Use of regional raw materials in the feeding of equine mature creoles in the municipality of Villavicencio.RESUMEN:  El presente trabajo fue realizado en Catama, Municipio de  Villavicencio. Se utilizaron 9 caballos criollos, adultos, machos,  castrados. El ensayo fue dividido en dos fases en las que se evaluaron tres raciones; 1. Ración comercial, como testigo; 2.Ración con 12,4% de pica de arroz y sin aceite crudo de palma africana, ACPA  y 3. Ración con 0,86% de ACPA y 20,8% de pica de arroz. Fue   empleado  un diseño experimental   totalmente  al azar de tres tratamientos con tres  repeticiones.  En la  primera  fase  experimental  se  evalúo  ganancia  de  peso,  condición  corporal y estado  físico. En la segunda  fase se determinó  la  digestibilidad total aparente de las raciones,  por el método de colecta  total de heces; también se estimó la proteína sérica total pre y  postprandial  en horas 0, 1, 2, 3  y  4.  No se encontraron  diferencias significativas (P>0.05) en la ganancia  de peso ni en la digestibilidad de las diferentes  raciones.  Los valores de las proteínas  séricas  totales  fue similar en todos  los tratamientos. Se concluye que en equinos adultos  de trabajo  liviano dietas  con 12.4% de pica de arroz y sin ACPA, presentan mejor ganancia  de peso y mayor digestibilidad de materia  seca y fibra cruda.Palabras clave: Aceite, Arroz, equinos,  digestibilidad total.ABSTRACT:  The present  work was carried out in Catama,  which is in the municipality of Villavicencio. Nine adult creoles castrated male horses were used. The feeding trial was divided in two phases  during which three different rations were evaluated;  1. a commercially prepared  ration was  used as a control; 2. a ration with 12.4% of rice fibres by product (pica)  without palm oil; 3. a ration with 0,86% of palm oil and 20,8% of rice fibres by product(pica). These rations were used at random in an experimental  design of three treatments with three repetitions.  In the first  experimental  phase,  the  horses  were  evaluated  for weight  gain,   corporal  condition,  and  physical  state. During the second phase,   apparent total digestibility was determined  by the method of total  collection of feces, and also total serum protein was also measured in the  three treatments pre and postprandial  in hours 0, 1, 2, 3, and 4. No  significant differences (P >0.05) where encountered  in the weight gains,  nor in the digestibility of the different rations. The data of the total serum  protein was similar in all the treatments. In conclusion,  for equine adults  doing light work, the best results were obtained with the ration with 12.4%  of rice (pica de) without palm oil resulted in the best weight gain, and  greater digestibility of dry matter  and raw fiber.Key words: horses,  total digestibility, oil, rice.